Olokizumab, a monoclonal antibody against interleukin-6, in combination with methotrexate in patients with rheumatoid arthritis inadequately controlled by tumour necrosis factor inhibitor therapy: efficacy and safety results of a randomised controlled phase III study - E. Feist; S. Fatenejad; S. Grishin; E. Korneva; M.E. Luggen; E. Nasonov; M. Samsonov; J.S. Smolen; R.M. Fleischmann (Современная ревматология)
Objectives To assess the efficacy and safety of olokizumab (OKZ), a monoclonal antibody against the interleukin-6 (IL-6) cytokine, versus placebo (PBO) in patients with prior inadequate response to tumour necrosis factor inhibitors (TNFi-IRs).Methods In this 24-week multicentre, placebo-controlled, double-blind study, the patients were randomised in a 2:2:1 ratio to receive subcutaneously administered OKZ 64 mg once every 2 weeks (q2w), OKZ 64 mg once every 4 weeks (q4w) or PBO plus methotrexate. At week 16, the patients on PBO were randomised to receive either OKZ regime. The primary endpoint was the proportion of patients achieving an American College of Rheumatology 20% (ACR20) response at week 12. Disease Activity Score 28-joint count C-reactive protein (DAS28 (CRP)) <3.2 at week 12 was the major secondary efficacy endpoint. Safety and immunogenicity were assessed.Results In 368 patients randomised, ACR20 response rates were 60.9% in OKZ q2w, 59.6% in OKZ q4w and 40.6% in PBO (p<0.01 for both comparisons). Achievement of DAS28 (CRP) <3.2 was significantly different, favouring the OKZ arms. Improvements in efficacy and patientreported outcomes were maintained throughout 24 weeks and were noted after week 16 in patients who switched from PBO.Dose-related treatment-emergent serious adverse events were 7% in OKZ q2w, 3.2% in OKZ q4w and none in the PBO group.Conclusions Direct inhibition of IL-6 with OKZ resulted in significant improvements in the signs and symptoms of rheumatoid arthritis compared with PBO in TNFi-IR patients with a similar safety profile as observed for monoclonal antibodies to the IL-6 receptor.